(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
This study investigated the effect of plant feedstock– and animal feedstock–derived biochar at 10%w/w and 15%w/w amendment levels on the biostimulation efficiency and the cultivable microbial community in the soil during biochar-facilitated remediation of petroleum contaminated soil using standard techniques. Biostimulation was most effective with the animal-based biochar (ABB) treatment while total petroleum hydrocarbon (TPH) removal was greatest in the plant-based biochar (PBB) amended soil. Observed mean TPH levels on Day 60 ranged from about 7000 mg/kg – 7800 mg/kg for the PBB and 11000 mg/kg – 14000 mg/kg for ABB representing removal levels of roughly 51.0%, 57.7%, 72.4% and 73.7% in 10% ABB, 15% ABB, 10% PBB and 15% PBB amended contaminated soils respectively. The cultivable bacterial diversity for both feedstock types shifted from the combination of Firmicutes, Actinobacteria and Proteobacteria phyla at the onset of the study to predominantly Proteobacteria by the end of the study with a distinct reduction in diversity observed with increasing contact time. The dominant cultivable heterotrophic bacterial isolates were Bacillus spp., Pseudomonas spp. and Staphylococcus aureus for ABB and Pseudomonas spp., Klebsiella pneumoniae and Bacillus spp. for PBB. Amongst the cultivable hydrocarbon utilising bacteria obtained, Klebsiella pneumoniae, Pseudomonas spp. and Enterobacter spp. dominated. There were significant differences in TCHB and CHUB abundance and TPH removal efficiency between PBB and ABB amendments at 95% confidence interval. The study established that application of biochar effectively manages petroleum pollutants in soil by stimulating the proliferation and activities of relevant degradative species.